Accountability Analysis of Subulussalam City Grants and Social Assistance - Handayani, Alum; ikhsan, ikhsan (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
This research will discuss accountability in the provision of grants and social assistance in the City of Subulussalam. Accountability is a form of success or failure in carrying out mandatory responsibilities and carrying out tasks through regular accountability media. This research uses a qualitative method with field studies through observation, interviews, and documentation, the reason for choosing this method is because researchers can see firsthand how accountability for grants and social assistance is in the City of Subulussalam. Accountability in the provision of grants and social assistance is seen through indicators of public accountability according to Manggaukung Raba (2006), namely by looking at legitimacy for policymakers, the existence of adequate moral quality, sensitivity, openness, optimal use of resources, efficiency, and effectiveness.